The Travels of Sir John Mandeville - Mandeville, John, Sir (Salt Lake City, UT : Project Gutenberg, 1997)
"The Travels of Sir John Mandeville" by Sir John Mandeville is a travelogue written between 1357 and 1371 that claims to chronicle an Englishman's journey across the Near East to India and China. Blending fact with fantasy, this extraordinarily popular medieval work drew from various sources including Odoric of Pordenone and Armenian monk Hetoum. Though "Sir John Mandeville" was likely an invented author and many travels described are unreliable or fantastical, the book profoundly influenced explorers like Christopher Columbus, serving as a curious mix of pilgrimage guide and exotic wonder tale. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mandeville%27s_Travels
Itinerarium
Release date is 1997-01-01
Transcribed from the 1900 Macmillan and Co. edition by David Price
Translated from Anglo-Norman
Keywords: Voyages and travels -- Early works to 1800; Mandeville, John, Sir -- Travel; Geography, Medieval; Palestine -- Description and travel -- Early works to 1800; Orient -- Description and travel -- Early works to 1800